Identification of a Novel Partitivirus of Trichoderma harzianum NFCF319 and Evidence for the Related Antifungal Activity - Chun, Jeesun; Yang, Han-Eul; Kim, Dae-Hyuk (Frontiers in Plant Science, 2018)
We have reported 15 agarose gel band patterns of double-stranded RNA (dsRNA) from Trichoderma spp.. We describe herein that band pattern IX in Trichoderma harzianum NFCF319, which appeared to be a single band but consisted of two dsRNAs of similar size, was identified as a novel mycovirus, designated Trichoderma harzianum partitivirus 1 (ThPV1). The larger segment (dsRNA1) of the ThPV1 genome comprised 2,289 bp and contained a single open reading frame (ORF) encoding a RNA-dependent RNA polymerase (RdRp). The smaller segment (dsRNA2) consisted of 2,245 bp with a single ORF encoding capsid protein (CP). Evaluation of the deduced amino acid sequence and phylogenetic analysis indicated that ThPV1 is a new member of the genus Betapartitivirus in the family Partitiviridae. Curing of virus infection by single-sporing generated 31 virus-free single-spore clones. No significant differences in growth rate, conidia production, or pigmentation were observed between ThPV1-infected and -cured isogenic strains. In addition, comparison of the newly ThPV1-transmitted isolates with their ThPV1-cured parental strain showed no significant difference in colony morphology or pigmentation. However, inhibition of growth in co-cultured Pleurotus ostreatus and Rhizoctonia solani by T. harzianum was increased in ThPV1-containing strains compared with ThPV1-cured isogenic strains. Moreover, -1,3-glucanase activity was significantly increased in the ThPV1-containing strains. However, no difference in chitinase activity was observed, suggesting that ThPV1 regulates the activity of a specific fungal enzyme.